A need for cybercrime-specific legislation to address cybercrime as a new phenomenon of crime (2012)
Cybercrime portrays a new concept of crime that needs to be specially addressed by the law. The ways and the avenues of commission of this type of crime are remarkably different from the traditional means of committing crime, though sometimes the same consequence may result irrespective of the method adopted, only that the gravity may differ. The aim of this research is therefore to address the phenomenon of cybercrime in order to determine if the crime needs special legislative provisions different from the traditional crime statutes applicable in Nigeria